The importance of personal and collective resources in coping with stressors related to industrial action at the Coldstream sawmill - Besseling, Elizabeth Anne (Rhodes University, Faculty of Humanities, Department of Psychology, 1999)
The main purpose of the study is to investigate whether the stress response moderators served as effective variables in reducing the stress of the strike. For instance, if individuals differ in' their ability to actualise resources, does someone with a high SOC utilise friendships or supportive relationships more than someone with a low SOC? Does someone who has a high score for religious practice become less depressed when faced with a significant stressor than someone less involved in church activities?
Keywords: Stress (Psychology); Stress (Physiology); Industrial relations -- South Africa -- Case studies; Coldstream (South africa)